Physical activities and contributions to the prevention of chronic non-communicable diseases - Patrício, Diego Silva; Hilgemberg , Glaucia Renee; Marques, Luiz Henrique dos Santos da Cruz; Maceno , Marcelo Bruno da Silva; Matias, Joelma Maria Freire; Carvalho, Leandro Paim da Cruz; Menezes, Marco Tulio Soares; Cordeiro , Leiliane de Carvalho; Nour, Guilherme Frederico Abdul; Silva, Jéssica de Paula da (Seven Editora, 2024)
The objective of this research was to analyze the contributions of physical activities to the prevention of chronic non-communicable diseases. The study adopted an integrative review approach, using Google Scholar and Scielo databases with specific search criteria. Brazilian scientific articles published between 2022 and 2023 were selected and submitted to an analysis of titles and abstracts followed by a thorough reading to identify and synthesize the relevant results. As a result, the relevance of regular physical activity in the prevention and control of chronic non-communicable diseases (NCDs) was verified. Both aerobic and anaerobic activities are highlighted as key in reducing the risk factors associated with these conditions. The benefits of physical activity include improvements in cardiovascular and respiratory capacity, as well as reduced risk of various chronic conditions such as obesity, type 2 diabetes, cardiovascular disease, and cancer, contributing to improved quality of life and mental well-being. A significant finding is the observation that risk factors tend to increase when physical activity is stopped, emphasizing the need for consistency in these healthy habits. The importance of health awareness and education is also highlighted, especially among men, to overcome barriers to the adoption of healthy habits. Ultimately, the studies reinforce the importance of physical activity as a crucial tool in health promotion and prevention of NCDs, underlining the need for health policies and programs that encourage and facilitate its practice for a healthier and more resilient population in the long term. DOI:https://doi.org/10.56238/sevened2024.007-087